EDUKASI KEPADA MASYARAKAT TERKAIT TERAPI STROKE ISKEMIK DI KEC. GUNUNG MALIGAS KAB. SIMALUNGUN - Dian Permata Nasution; Marolop Parlindungan Napitu; Yeni Trisna Purba; Isa Harpika Br. Ginting; Hendri, Hendri (Yayasan Nusantara Hasana Berdikari, 2024)
This community service report discusses an educational activity on ischemic stroke therapy conducted in Gunung Maligas District, Simalungun Regency. The activity aimed to improve public knowledge and awareness regarding systemic therapy in ischemic stroke, particularly emphasizing the critical golden period for intravenous thrombolytic (IV tPA) administration and other supportive medication management. The methods included pre-tests, audiovisual lectures, interactive discussions, and distribution of educational leaflets. The activity results demonstrated a significant increase in participants’ knowledge, as measured by comparing pre-test and post-test scores. This initiative also provides a foundation for secondary prevention and improved stroke management within the community.